LEARNING OF DIVISION OPERATION FOR MENTAL RETARDATIONS’ STUDENT THROUGH MATH GASING - Nuari, Laila Fatika; Prahmana, Rully Charitas Indra; Fatmawati, Irma (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2019)
This study aims to look at tenth-grade a mental retardation student in solving the problem of a division operation. The method used is Single Subject Research (SSR) with learning outcomes as variables that are measured and describe student learning activities in solving problems using Math GASING. The data collection technique is done by video recorder, documentation and test questions. The instruments are a video that is to see student activities during the study, photos to see the results of student work, and work the answer to see student answers to the questions given. Analysis of this research data is analyzed in conditions and between conditions. The results of the research carried out obtained that student experienced an increase in solving the division questions and the student gave a good response to the behavior carried out with Math GASING.